Kontekstualisasi Pendidikan Kritis Berbasis Pemikiran Ali Syari’ati di Indonesia - Susanto, Nanang Hasan; Suyuti, Imam - (UIN Walisongo Semarang, 2018)
This paper aims to find out the contextualization of the critical ideology of Ali Syari'ati in the field of Islamic education. This paper uses a qualitative approach by gathering various literature on Ali Syari'ati's critical thinking, then analyzing it in the context of national education in Indonesia. The results of the study show that: first, education must be able to free humans from all forms of colonialism. second: the aim of critical education is to create an independent person and become a social prophet (rushan fekr) whose duty is to bring the people towards the desired ideals together, namely social welfare, free from acts of tyranny and misery of the people. third: making enlightened students that they are able to get out of four social prisons which include nature, history, society and human ego. In the context of Islamic education in Indonesia it can be realized by shaping students to be highly critical, independent and socially conscious individuals.Keywords: critical education; Ali Shari'ati; independent; social awareness; human ego; Islamic education; Indonesia; AbstrakTulisan ini bertujuan untuk mengetahui kontekstualisasi ideologi kritis Ali Syari’ati dibidang pendidikan Islam. Tulisan ini menggunakan pendekatan kualitatif dengan mengumpulkan berbagai literatur mengenai pemikiran kritis Ali Syari’ati, kemudian dianalisis dalam konteks pendidikan Nasional di Indonesia. Hasil penelitian menunjukkan bahwa: pertama, Pendidikan harus dapat membebaskan manusia dari semua bentuk penjajahan. kedua: tujuan pendidikan kritis adalah untuk mewujudkan pribadi yang merdeka dan menjadi nabi sosial (rushan fekr) yang bertugas untuk membawa umat menuju cita-cita yang diinginkan bersama, yaitu kesejahteraan sosial, terbebas dari tindak kezaliman dan kesengsaraan umat. ketiga: menjadikan siswa yang tercerahkan yaitu mereka mampu keluar dari empat penjara sosial yang meliputi sifat dasar, sejarah, masyarakat, dan ego manusia. Dalam konteks pendidikan Islam di Indoenesia bisa diwujudkan dengan membentuk anak didik menjadi pribadi yang kritis, independen dan berkesadaran sosial yang tinggi.Kata Kunci: pendidikan kritis; Ali Syari’ati; independen; kesadaran social; ego manusia; pendidikan Islam; Indonesia